An Analysis of Code Mixing and Code Switching Used in Maudy Ayunda's YouTube Channel Video - Lestari, Ni Putu Diana Eka; Artini, Luh Putu; Sri Adnyani, Ni Luh Putu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The phenomenon of code mixing and code switching takes place in bilingual or multilingual societies. These phenomena occur not only in direct communication but also virtually on social media platforms, such as YouTube. This study was grounded in the theoretical frameworks of Hoffman (1991), who identifies three distinct types of code mixing: intra-sentential code mixing, intra-lexical code mixing, and code-mixing involving pronunciation change. Meanwhile, types of code switching are classified into tag switching, intra-sentential code switching, and inter-sentential code switching (Wei, 2007). This study analyzed the types of code mixing and switching used in one of Maudy Ayunda's YouTube Channel videos entitled "How I manage Stress – Maudy Ayunda," published on October 21, 2020, with a duration of 10 minutes and 44 seconds. It analyzed the qualitative content of one of Maudy Ayunda's YouTube videos. Data were collected by selecting and watching the video, transcribing it, identifying code mixing and code switching within the video, and re-checking the video. Then, the data were analyzed using Miles and Huberman's theory (2014) through data reduction, data presentation, and conclusion. The study's findings revealed that code mixing and code switching were present in Maudy Ayunda's video, where 14 expressions were categorized as code mixing and 12 as code switching. The types of code mixing found in the video were intra-sentential and intra-lexical code mixing. Meanwhile, the kinds of code switching observed in the video included intra-sentential, inter-sentential, and tag switching. This study contributed to understanding how code mixing and code switching occur on social media platforms like YouTube by highlighting the different types of people commonly used in online communication. Future research is encouraged to include more videos or speakers to provide richer and more comprehensive data, as the current study is limited to a single video from a single public figure.